Crescimento, fisiologia e produção da melancieira sob irrigação com águas salinas e adubação orgânica - Bezerra, Jeferson Dutra (2017)
The great majority of plants of high economic value exhibit sensitivity to soil salts and irrigation water, thus justifying the need for research that involves alternatives to overcome the deleterious effects of salinity on plants. The objective of this experiment was to evaluate the behavior of watermelon irrigated with saline water and fertilized with bovine manure, based on physiological variables of gas exchange and photosynthetic pigments. The experiment was carried out in a randomized block design in the 5 x 2 factorial scheme, referring to five levels of electrical conductivity of irrigation water (0.3, 1.3, 2.3, 3.3, and 4.3 dS m-1) without and with the application of manure -winter, with four replicates and three useful plants per plot. Stomatal conductance, transpiration, liquid photosynthesis, internal CO2 concentration, and the instantaneous efficiency of water use by the A / E ratio, and the instantaneous efficiency of carboxylation by the A / Ci ratio were estimated. Chlorophyll a, chlorophyll b, total chlorophyll, carotenoids, chlorophyll a + b, chlorophyll a / b and extravasation of electrolytes were also quantified. The data were submitted to analysis of variance. The manure averages were compared by the F test. For the electrical conductivity, a polynomial regression analysis was performed. Analyzes of major components were also performed. The increase in the electrical conductivity of the irrigation water decreased the levels of photosynthetic pigments and increased the extravasation of cellular electrolytes, reducing the photosynthetic efficiency in plants of watermelon. The application of bovine manure in the soil attenuated the effect of saline stress only on chlorophyll b and carotenoids. The salinity of the water inhibited the gas exchanges, with greater effect on the stomatal conductance, liquid photosynthesis and the transpiration of the plants.